Assessing Chronotypes by Ambulatory Circadian Monitoring - Martinez-Nicolas, Antonio; Martinez-Madrid, Maria Jose; Almaida-Pagan, Pedro Francisco; Bonmati-Carrion, Maria-Angeles; Madrid, Juan Antonio; Rol, Maria Angeles (Frontiers in Physiology, 2019)
In order to develop objective indexes for chronotype identification by means of direct measurement of circadian rhythms, 159 undergraduate students were recruited as volunteers and instructed to wear ambulatory circadian monitoring (ACM) sensors that continuously gathered information on the individual’s environmental light and temperature exposure, wrist temperature, body position, activity and the integrated TAP (Temperature, Activity and Position) variable for 7 consecutive days under regular free-living conditions. Among all the proposed indexes, the night phase marker (NPM) of the TAP variable was the best suited to discriminate among chronotypes, due to its relationship with the Munich ChronoType Questionnaire (β=0.531; p<0.001). The NPM of TAP allowed subjects to be classified as Early- (20%), Neither- (60%) and Late-types (20%), each of which had its own characteristics. In terms of light exposure, while all subjects had short exposure times to bright light (>100 lux), with a daily average of 93.84±5.72 minutes, the earlier chronotypes were exposed to brighter days and darker nights as compared to the later chronotypes. Furthermore, the earlier chronotypes were associated with higher stability and day-night contrast, along with an earlier phase, which could be the cause or consequence of the light exposure habits. Overall, these data support the use of ACM for chronotype identification and for evaluation under free living-conditions, using objective markers.